Information about the Siberian Murza of the Kulmametevs in the light of the Generational Painting of the Late 18th Century - Z. A. Tychinskikh (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article considers the early stage of the history of the famous Siberian Murza genus Kulmametevs. Documents from the central, regional and local archives became the material for publication, the main of which was the generation of paintings - a document from the State Archives of the Perm Territory, dating to the end of the 18th century and containing information about the service representatives of the genus. Based on the analysis of the complex of various sources, individual moments of the genealogy from the end of the 16th to the 18th century are identified and refined. The origin of the Kulmametevs from Prince Begish of the era of the Siberian Khanate is proved. Based on the analysis of the complex of various sources, individual moments of the genealogy from the end of the 16th to the 18th century are identified and refined. The origin of the Kulmametevs from Prince Begish of the era of the Siberian Khanate is proved. As the prospects of the study the significance of the results obtained for studying both individual significant representatives of the Turkic population of Western Siberia after its inclusion in the Russian state and the features of the formation of the upper stratum of this population, building relations between the top of the serving Tatars and the Russian administration is emphasized.